Assessing Bachelor-Level Students’ Interest in Daytime Non-Credit Skill- Based Courses: A Survey Study at Mahakavi Devkota Campus - G. C., Prakash; Karna, Suraj Kumar (Devkota Journal of Interdisciplinary Studies, 2026)
This study investigates bachelor-level students’ interest in daytime non-credit skill-based courses at Mahakavi Devkota Campus. In contemporary higher education, academic degrees alone are often insufficient to meet the rapidly changing demands of the labor market. Students increasingly seek additional practical, technical, and entrepreneurial competencies that can improve employability and career readiness. In this context, non-credit short courses provide a flexible and accessible opportunity for learners to acquire market-relevant skills without increasing the burden of formal academic programs. The study employed a descriptive survey design and collected data from 136 bachelor-level students enrolled in different programs, including BBA, BBS, BA, B.Ed., and BICTE. A structured questionnaire was used to gather information regarding students’ awareness, previous exposure, level of interest, preferred course categories, class timing preferences, motivation, and willingness to pay. Data were analyzed using frequencies, percentages, and interpretive discussion. The findings reveal that although most students had limited prior experience with non-credit courses, a significant majority expressed strong interest in enrolling in such programs. Digital Marketing, Graphic Design, and Share Market-related courses emerged as the most preferred areas, followed by hospitality-oriented skills such as Barista and Bakery training. Students preferred classes during mid-morning and afternoon hours, indicating the practicality of daytime scheduling. Most respondents also favored an affordable fee range of NPR 10,000–12,000 for a three-month course. The study concludes that there is clear demand for structured, affordable, and career-oriented non-credit courses at Mahakavi Devkota Campus. Introducing such programs can strengthen students’ practical competence, improve employability prospects, and enhance the campus’s role in skill development and lifelong learning.